1967
DOI: 10.1021/jf60154a033
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated hydrocarbon insecticide residues in selected insects and birds found in association with cotton fields

Abstract: Insecticide residues were detected in 10 of the 15 insect species examined. The most common insecticide residues were , 'and its metabolite , '-.. The concentrations ranged from 0.10 to 9.16 p.p.m. and from a trace to 12.89 p.p.m., respectively. Aldrin, dieldrin, endrin, heptachlor epoxide, chlordane, and toxaphene also were present in some samples. Laboratory studies on the persistence of DDT in Heliothis spp. showed the fast disappearance of DDT, followed by the disappearance of DDE. There was no change in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…El Sayed et al (1967) found DDT residues in the fat of certain bird species associated with Louisiana cotton fields. Total DDT residues ran as high as 170 ppm in a house sparrow Seven bobwhite quail collected from selected environments in Louisiana contained residues of DDT and its metabolites ranging from 0.01 to 1.090 ppb (Epps et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…El Sayed et al (1967) found DDT residues in the fat of certain bird species associated with Louisiana cotton fields. Total DDT residues ran as high as 170 ppm in a house sparrow Seven bobwhite quail collected from selected environments in Louisiana contained residues of DDT and its metabolites ranging from 0.01 to 1.090 ppb (Epps et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…El Sayed et al (87) determined organochlorinated insecticide residues in select insects and birds found in cotton fields.…”
Section: T H Imentioning
confidence: 99%